2020
DOI: 10.1002/jctb.6590
|View full text |Cite
|
Sign up to set email alerts
|

Local volumetric mass transfer coefficient estimation for Scenedesmus microalgae culture in a cylindrical airlift photobioreactor

Abstract: A plug flow model without axial dispersion was utilized to evaluate the mass transfer coefficient in Scenedesmus microalgae culture grown in a split airlift photobioreactor. The local volumetric mass transfer coefficient and the local interfacial area also were calculated at various gas velocity (1.0, 2.0 and 2.8 cm s–1). In the riser and the downcomer section, the local volumetric mass transfer coefficients were dominated by interfacial area and gas holdup values, and were favored by lower optical densities (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Air plus 3% of CO 2 gases were injected through the sparger into the algal culturing system under ambient conditions at superficial gas velocity 3.0 cm s −1 . For harvest light, eight selected cool fluorescent lamps from Future Harvest Development were supported around the PBR to provide a surface PFD of 350–400 μE m −2 s −1 as recommended by Ojha and Al‐Dahhan 56 and Ojha et al 57 …”
Section: Methodsmentioning
confidence: 99%
“…Air plus 3% of CO 2 gases were injected through the sparger into the algal culturing system under ambient conditions at superficial gas velocity 3.0 cm s −1 . For harvest light, eight selected cool fluorescent lamps from Future Harvest Development were supported around the PBR to provide a surface PFD of 350–400 μE m −2 s −1 as recommended by Ojha and Al‐Dahhan 56 and Ojha et al 57 …”
Section: Methodsmentioning
confidence: 99%
“…Several models describing microalgae response to light have been proposed in the literature, in some cases including investigation of mass transfer [9,10]. Béchet et al [11] suggested classification into three categories according to how the photosynthetic productivity is computed.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 5.Specific growth rate versus different irradiation intensities of the microalga Nannochloropsis gaditana in the quasi-isoactinic photobioreactor: black circles, experimental data; line, Equation(10).…”
mentioning
confidence: 99%
“…In a multiphase system, the phase holdup is described as the volume fraction occupied by the system phase considered [41][42][43][44].…”
Section: Phase Holdupmentioning
confidence: 99%